Reaction of diaryl-1,2-diones with triphenylphosphine and diethyl azodicarboxylate leading to N, N-dicarboethoxy monohydrazones via a novel rearrangement - Nair, Vijay; Biju, Akkattu T.; Abhilash, K. G.; Menon, Rajeev S.; Eringathodi, Suresh (Organic Letters, 2005)
A mechanistically novel reaction of diaryl-1,2-diones with diethyl azodicarboxylate and triphenylphosphine to afford N,N-dicarboethoxy monohydrazones is described. The reaction proceeds via a nitrogen to nitrogen migration of a carboethoxy group.

Reaction of huisgen zwitterion with 1,2-benzoquinones and isatins: expeditious synthesis of dihydro-1,2,3-benzoxadiazoles and spirooxadiazolines - Nair, Vijay; Biju, Akkattu T.; Vinod, A. V.; Eringathodi, Suresh (Organic Letters, 2005)
The zwitterionic intermediate generated from dialkyl azodicarboxylate and triphenylphosphine on reaction with 3-methoxy-1,2-benzoquinones afforded dihydro-1,2,3-benzoxadiazoles. N-Substituted isatins furnished spirooxadiazolines under similar conditions.

Reaction of huisgen zwitterion with diaryl-1,2-diones and ketones: an efficient protocol for carbon-nitrogen bond formation - Nair, Vijay; Biju, Akkattu T.; Mathew, Smitha C. (Synthesis-Stuttgart, 2007)
The reaction of Huisgen zwitterion, derived from triphenylphosphine and dialkyl azodicarboxylate, with diaryl-1,2-diones afforded N,N-dicarboalkoxy monohydrazones via a mechanistically novel rearrangement. Cyclic and acyclic ketones furnished vinyl hydrazinedicarboxylates under similar conditions.
Keywords: betaines - diazo compounds - hydrazones - ketones - rearrangements

Reaction of tpp-azodicarboxylate zwitterions and aldehydes: unprecedented synthesis of acyl carbamates - Nair, Vijay; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh (Tetrahedron Letters, 2007)
An efficient synthesis of acyl carbamates from aryl aldehydes by the reaction of triphenylphosphine and dialkyl azoesters is described.

Reaction of huisgen zwitterion with diaryl ketones leading to the facile synthesis of mono- and bis(alkoxycarbonyl)hydrazones - Nair, Vijay; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh (Synthesis-Stuttgart, 2008)
The Huisgen zwitterion, generated from triphenylphosphine and dialkyl azodicarboxylates, afforded upon reaction with diaryl ketones both mono- and bis(alkoxycarbonyl)hydrazones, depending on the reaction conditions.

Reactions of morita-baylis-hillman acetates with huisgen zwitterions: a novel strategy for the synthesis of ?-amino acid derivatives - Jose, Anu; Paul, Rony Rajan; Mohan, Resmi; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh; Nair, Vijay (Synthesis, 2009)
The reaction of Huisgen Zwitterion with Morita–Baylis– Hillman acetates afforded b-amino acid derivatives.
Keywords: b-amino acid; Huisgen zwitterion; Morita–Baylis–Hillman acetate

Recent advances in transition-metal-free carbon-carbon and carbon-heteroatom bond-forming reactions using arynes - Bhunia, Anup; Yetra, Santhivardhana Reddy; Biju, Akkattu T. (Chemical Society Reviews, 2012)
This tutorial review is aimed at highlighting recent developments in transition-metal-free carbon-carbon and carbon-heteroatom bond-forming reactions utilizing a versatile class of reactive intermediates, viz., arynes, which hold the potential for numerous applications in organic synthesis. Key to the success of the resurgence of interest in the rich chemistry of arynes is primarily the mild condition for their generation by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates. Consequently, arynes have been employed for the construction of multisubstituted arenes with structural diversity and complexity. The versatile transition-metal-free applications of arynes include cycloaddition reactions, insertion reactions and multicomponent reactions. In addition, arynes have found applications in natural product synthesis. Herein, we present a concise account of the major developments that occurred in this field during the past eight years.

Rapid access to benzoxaphospholes and their spiro analogues by a three-component coupling involving arynes, phosphines, and activated ketones - Bhunia, Anup; Roy, Tony; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2014)
An operationally simple multicomponent coupling involving in situ generated arynes from 2 (trimethylsilyl)aryl triflates, phosphines, and various acyclic and cyclic activated carbonyl compounds has been developed. The reaction proceeds via a formal [3 + 2] cycloaddition mode giving access to differently substituted (spiro)benzoxaphosphole derivatives in moderate to good yields Mild reaction conditions. a broad scope. and the possibility of varying all the three-components are the notable features of the present reaction.

Reaction of N-heterocyclic carbenes with chalcones leading to the synthesis of deoxy-breslow intermediates in their oxidized form - Bhunia, Anup; Thorat, Shridhar H.; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2015)
The synthesis of deoxy-Breslow intermediates in their oxidized form has been developed via the reaction of N-heterocyclic carbenes (NHCs) with chalcones. Moreover, the initial tetrahedral adduct formed from the 1,4-addition of NHCs to chalcones is also isolated.

Recent advances in employing homoenolates generated by N-heterocyclic carbene (NHC) catalysis in carbon-carbon bond-forming reactions - Menon, Rajeev S.; Biju, Akkattu T.; Nair, Vijay (Chemical Society Reviews, 2015)
The use of NHCs for generating homoenolate species has gained widespread popularity in recent years. A number of highly stereoselective processes of NHC-homoenolates have emerged. Homoenolate reactions have also been employed as key steps in the total synthesis of a number of natural products. The use of compatible co-catalysts, improved NHC-catalyst design and the use of novel precursors for homoenolate generation are among the major developments in this area that were disclosed recently. This tutorial review organises and presents the advancements in this rapidly growing area of catalysis and in the process updates a previous account published in 2011 in this journal.

Recent advances in the N-heterocyclic carbene (NHC)-organocatalyzed stetter reaction and related chemistry - Yetra, Santhivardhana Reddy; Patra, Atanu; Biju, Akkattu T. (Synthesis‐Stuttgart, 2015)
Recent developments in the N-heterocyclic carbene (NHC)-catalyzed umpolung of aldehydes followed by their interception with activated carbon–carbon double bonds, namely the Stetter reaction, are presented. Advances in the inter- and intramolecular versions of this reaction, enantioselective transformations as well as the use of unactivated olefins in this type of reaction are discussed.

Recent advances in N-heterocyclic carbene (NHC)-catalysed benzoin reactions - Menon, Rajeev S.; Biju, Akkattu T.; Nair, Vijay (Beilstein Journal of Organic Chemistry, 2016)
N-Heterocyclic carbenes (NHCs) have emerged as a powerful class of organocatalysts that mediate a variety of organic transformations. The Benzoin reaction constitutes one of the earliest known carbon-carbon bond-forming reactions catalysed by NHCs. The rapid growth of NHC catalysis in general has resulted in the development of a variety of benzoin and benzoin-type reactions. An overview of such NHC-catalysed benzoin reactions is presented.
Keywords: acyloin reaction; benzoin reaction; N-heterocyclic carbenes; organocatalysis; umpolung

Recent advances in N-heterocyclic carbene (NHC)-catalysed benzoin reactions (vol 12, pg 444, 2016) - Menon, Rajeev S.; Biju, Akkattu T.; Nair, Vijay (Beilstein Journal of Organic Chemistry, 2016)
Keywords: acyloin reaction; benzoin reaction; N-heterocyclic carbenes; organocatalysis; umpolung

Recent advances in molecular rearrangements involving aryne intermediates - Roy, Tony; Biju, Akkattu T. (Chemical Communications, 2018)
This Feature Article is aimed at highlighting the recent developments in the transition-metal-free molecular rearrangements involving arynes. The chemistry of arynes has shown incredible developments especially in transition-metal-free carbon-carbon and carbon-heteroatom bond-forming reactions in the last three decades. The rapid growth in this field is mainly due to the development of mild methods for the generation of arynes. One aspect of the recent developments in the chemistry of arynes involves the molecular rearrangements proceeding via this electrophilic intermediate. The molecular rearrangements have provided direct access to a library of valuable molecules, which cannot be accessed in a single step through other synthetic routes. Herein, we present a concise account on the developments that occurred in this field over the last three decades.

Recent advances in the organocatalytic enantioselective synthesis of functionalized -lactones - Mukherjee, Subrata; Biju, Akkattu T. (Chemistry-An Asian Journal, 2018)
This Focus Review highlights recent developments in the organocatalytic enantioselective synthesis of -lactone derivatives. Owing to the importance of -lactones as a heterocyclic motif that is present in a variety of natural products and biologically active molecules, several catalytic methods have been developed for the synthesis of these compounds in their enantiomerically pure form. Organocatalytic methods that employ N-heterocyclic carbenes (NHCs), cinchona alkaloids, isothioureas, 4-dimethylaminopyridine (DMAP) derivatives, and phosphines have allowed the highly enantioselective synthesis of -lactones from cheap and readily available starting materials. Moreover, the inherent strain in the four-membered ring of -lactones has also been utilized in further synthetic transformations, thus making -lactones a versatile intermediate in organic synthesis.

Rapid synthesis of zwitterionic phosphonium benzoates by a three-component coupling involving phosphines, arynes and CO2 - Bhattacharjee, Subrata; Raju, Anjali; Gaykar, Rahul N.; Gonnade, Rajesh G.; Roy, Tony; Biju, Akkattu T. (Chemistry-An Asian Journal, 2020)
A mild and easy to perform multicomponent coupling involving phosphines, arynes generated from 2-(trimethylsilyl)aryl triflates, and CO(2)allowing the transition-metal-free synthesis of zwitterionic phosphonium benzoates has been developed. The reaction proceeds via the generation of 1 : 1 zwitterionic intermediates from phosphines and arynes followed by the interception with CO(2)to deliver the carboxylates in moderate to good yields instead of the anticipated benzooxaphosphol-3(1H)-ones.
Keywords: arynes; Carbon dioxide; multicomponent coupling; Phosphines; zwitterions